Exploring the suitability of the evaluation criteria used in the MPT projects, by looking at hard and soft components of development programmes - Ncapai, Wandile (Rhodes University, Faculty of Humanities, Department of Sociology, 2002)
The study explores the suitability of the evaluation criteria used in Microprojects Programme Trust (MPT), by looking at hard and soft components of the development programme. In this sense hard components of development refer to those components of projects that are tangible and can be physically observed and can bring material changes to the life of the community. Soft components of development refer to those components of projects that bring qualitative transformation to the life of the community, i.e. increased levels of awareness, human well-being and the empowerment process that addresses the community's abstract needs, these are not tangible and often cannot be physically observed. Midway through its contract periods MPT evaluate all projects. The purpose of these mid term evaluations is to make recommendations to MPT on future approaches and methodology for community development and operations. The mid-term evaluation also influences the distribution and allocation of resources and funding. It was therefore vital that the criteria used are subject to tests and critical analysis so as to assess their validity. The assessment of the mid-term evaluation criteria used in MPT projects has been to further determine the appropriateness or suitability of the evaluation criteria as an instrument to measure and guide the MPT community development approach in the Eastern Cape. The method used was to conduct focus group discussions so as to get an insight into the local community situation as well as to assess non-tangible improvements and changes that have occurred in the life of the community as a result of the project. The information generated was used to compare what the community believe they achieved with what the official mid-term evaluation reports indicate was assessed and achieved and that was contrasted with what the literature recommends should have been assessed. The study found that the mid-term evaluations conducted on MPT projects have no social context in which the evaluations themselves were conducted. The terms of reference and criteria were based on the programme design which was formulated and compiled by the European Union without the participation of the local South African community. The findings also indicated that projects become unsuccessful or partly successful if the "soft" components which have a bearing on social and economic realities are neglected. The thesis ends with recommendations on how the mid-term evaluations as well as MPT programme can be developed to be more responsive to the needs as identified by the communities themselves. It is strongly believed that this study will provide a valuable contribution towards increasing the ability of MPT programme to bring about both material and qualitative transformation to the I ives of the disadvantaged community of the Eastern Cape whilst ensuring that the mid-term evaluations are developed and shaped to become an appropriate instrument to measure and guide MPT programme approach to community development.
Keywords: Community development -- South Africa -- Eastern Cape; Community development; Economic development -- South Africa -- Eastern Cape; Economic development projects -- South Africa -- Eastern Cape